2013
DOI: 10.3109/08880018.2013.778927
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Function in Female Survivors of Childhood Malignancies

Abstract: Female survivors of childhood malignancies had reduced ovarian reserve and reduced mean ovarian volume, especially those with older age, older age of menarche, and longer treatment duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A study of an AML cohort treated with chemotherapy alone (anthracyclines and cytarabine) demonstrated that menarche occurred at the mean age of 13.1 years and fertility rates were similar to their siblings (92). Even in the absence of exposure to API and despite the occurrence of menarche at a normal age, CCS were nevertheless shown to have a decreased reproductive capacity in comparison to healthy controls in another report (113). The risk of premature menopause was 8 and 0.8% (RR = 13.21, 95% CI = 3.26–53.51; p  < 0.001) in CCS and siblings, respectively (108).…”
Section: Disorders Of the Gonadsmentioning
confidence: 94%
See 2 more Smart Citations
“…A study of an AML cohort treated with chemotherapy alone (anthracyclines and cytarabine) demonstrated that menarche occurred at the mean age of 13.1 years and fertility rates were similar to their siblings (92). Even in the absence of exposure to API and despite the occurrence of menarche at a normal age, CCS were nevertheless shown to have a decreased reproductive capacity in comparison to healthy controls in another report (113). The risk of premature menopause was 8 and 0.8% (RR = 13.21, 95% CI = 3.26–53.51; p  < 0.001) in CCS and siblings, respectively (108).…”
Section: Disorders Of the Gonadsmentioning
confidence: 94%
“…Cancer treatments associated with ovarian toxicity include abdominopelvic irradiation (API) and chemotherapy agents such as cyclophosphamide, procarbazine, busulfan, melphalan, and thiotepa (107110). Chemotherapy is less toxic to the ovaries of pre-pubertal females in comparison to pubertal and adult females (107, 111113). The ovarian toxicity of API is age and dose dependent, irradiation doses >20 Gy in female, CCS >13 years old, and TBI in CCS > 10-years is correlated with ovarian insufficiency (107, 114, 115).…”
Section: Disorders Of the Gonadsmentioning
confidence: 99%
See 1 more Smart Citation
“…the fertility of young female cancer survivors because it causes irreversible premature ovarian insuffi ciency, which is defi ned as menopause before the age of 40 (El-Shalakany, Ali, Abdelmaksoud, El-Ghany, & Hasan, 2013). Th ere are very few chemotherapeutic agents that are capable of cell specifi city, but the alkylating agents have demonstrated the highest levels of gonadotoxicity.…”
Section: Continuing Nursing Education (Cne) Creditmentioning
confidence: 99%
“…This process is particularly devastating to ovarian cells because after destruction they are not capable of regeneration (Bedaiwy et al, ). The attack on female reproductive cells can have a large impact on the fertility of young female cancer survivors because it causes irreversible premature ovarian insufficiency, which is defined as menopause before the age of 40 (El‐Shalakany, Ali, Abdelmaksoud, El‐Ghany, & Hasan, ). There are very few chemotherapeutic agents that are capable of cell specificity, but the alkylating agents have demonstrated the highest levels of gonadotoxicity.…”
Section: Introductionmentioning
confidence: 99%